Real-world outcomes of sitagliptin and sitagliptin/metformin single-pill combination treatment in diverse type 2 diabetes populations (DIVERSITY study) - Andrej Janez; Mirjana Bojic; Tomislav Bozek; Zdravko Kamenov; Tatjana Milenkovic; Gabriela Radulian; Tamás Várkonyi (Frontiers in Clinical Diabetes and Healthcare, 2026)
Introduction Real-world evidence on dipeptidyl peptidase-4 (DPP-4) inhibitors is limited by selective populations in randomized trials. The international, prospective DIVERSITY study evaluated the effectiveness, safety, and treatment acceptability of sitagliptin and sitagliptin/metformin single-pill combination (SPC) in routine clinical practice across diverse type 2 diabetes (T2D) populations. Methods This non-interventional, multicenter study enrolled adults with T2D eligible for sitagliptin or sitagliptin/metformin SPC and followed them for 6 months with three data captures (baseline, ~3 months, ~6 months). The analysis set comprised 2,603 patients (mean age 64.6y ± 10.6; 53.1% women) meeting all criteria and with ≥152 days between first and third captures. Primary outcomes were absolute changes in glycated hemoglobin (HbA1c), fasting plasma glucose (FPG), and post-prandial glucose (PPG) from baseline to 6 months. Secondary outcomes included the proportion achieving HbA1c <7% at 3 and 6 months, changes in body mass index (BMI), and hypoglycemia incidence. Safety was assessed in all treated patients (safety analysis set [SAS], n=2,697). Results Glycemic control improved over the 6-month observation period. Among patients with paired data, mean HbA1c fell from 7.98% to 6.99% (Δ −0.99%, 95% CI −1.05 to −0.93). Reductions were observed with both regimens: sitagliptin monotherapy (Δ −0.93%, 95% CI −1.01 to −0.85) and sitagliptin/metformin SPC (Δ −1.03%, 95% CI −1.11 to −0.96). FPG decreased by −1.91 mmol/L (95% CI −2.03 to −1.79) and PPG by −2.39 mmol/L (95% CI −2.56 to −2.21). The share of patients with HbA1c <7% rose from 16.9% at baseline to 53.7% at 6 months. BMI changes were small and consistent with weight neutrality (mean −0.61 ± 1.33 kg/m²). Treatment-related symptoms of hypoglycemia were rare (3 cases [0.1%] of all treated patients) and treatment acceptability was high: ≥90% patients and investigators reported satisfaction at 6 months. Conclusions In routine practice across heterogeneous T2D populations, sitagliptin and sitagliptin/metformin SPC were associated with clinically meaningful improvements in HbA1c, FPG, and PPG over 6 months, with effects consistent with a weight-neutral profile, a low reported incidence of hypoglycemia, and high treatment satisfaction. These findings are consistent with the use of sitagliptin-based regimens, whether used as monotherapy or as add-on therapy, as treatment options in routine real-world care, including in older and multimorbid patients.